2007
DOI: 10.1038/sj.jp.7211830
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inhaled nitric oxide on pulmonary function in preterm infants

Abstract: Objective: Bronchopulmonary dysplasia (BPD) in preterm infants is associated with impaired alveolar growth, inflammation and airway hyperreactivity. In animal models of BPD, inhaled nitric oxide (NO) improves alveolar growth and inhibits airway smooth muscle proliferation. This study was designed to assess the effect of inhaled NO on resistance and compliance in ventilated preterm infants with evolving BPD.Study Design: Expiratory resistance and compliance of the respiratory system were measured in 71 ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Some reports have been published describing no significant effects of inhaled NO on respiratory system resistance in preterm infants [26,27], also affected by the respiratory syncytial virus [28]. Belik et al [29] showed that the content and the activity of the NOS competitor arginase in the rat lungs exhibit significant reduction with increasing age of the animals, from fetal life to newborns and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have been published describing no significant effects of inhaled NO on respiratory system resistance in preterm infants [26,27], also affected by the respiratory syncytial virus [28]. Belik et al [29] showed that the content and the activity of the NOS competitor arginase in the rat lungs exhibit significant reduction with increasing age of the animals, from fetal life to newborns and adults.…”
Section: Discussionmentioning
confidence: 99%
“…BPD is a multifactorial chronic lung disease characterized by prolonged oxygen dependency, increased airway flow resistance and airway reactivity, decreased dynamic compliance, decreased FRC, and may be associated with significant long‐term morbidity in later life. Pulmonary function testing using different methods has been reported in numerous studies of neonates with RDS and BPD to objectively evaluate baseline disease severity, history, and disease predictive value as well as the effect of interventions such as surfactant, steroids, theophylline, bronchodilators, diuretics, inhaled nitric oxide, and ventilation . A state‐of‐the art critical review, focusing on respiratory mechanics, has been published recently by Gappa et al to summarize and discuss available data on PFT's performed on neonates and infants with chronic lung disease .…”
Section: Clinical Applications and Usefulness Of Pulmonary Mechanicsmentioning
confidence: 99%
“…16 Di Fiore et al, reported that the mean Rrs level on inhaled nitric oxide in preterm infants was 231 ± 71 cmH 2 O・kg/L/s. 17 Therefore, a reference Rrs range between 150 and 350 cmH 2 O・kg/L/s is likely an optimal value for infants with CDH. Rrs levels higher than this range might indicate the presence of additional factors that complicate effective ventilation management.…”
Section: Discussionmentioning
confidence: 99%